Pricing of Power Derivatives - Foukal, Viktor (2015)
The main target of this thesis is to summarize and demonstrate the main characteristic of power markets and trying to find out electricity spot model. Thesis starts with definition of market subjects, typology of traded contracts and description of market development with focus on South Easter Europe. Thesis continues with development of consumption function and theoretical concepts of Demand/Capacity ratio which is used in short term/spot modeling and serve to identify a risk of potential increase in volatility. After deriving fundamental models I will continue with stochastic model - Volatility Regime model with Jump diffusion. I used all these knowledge and observed patterns in order to evaluate illiquid power options with daily settlement.